Characterization of the Cicatrization Process in Diabetic Foot Ulcers Based on the Production of Reactive Oxygen Species - Alberto López-Delis; Suélia de S. Rodrigues Fleury Rosa; Paulo Eduardo Narcizo de Souza; Marcella Lemos Brettas Carneiro; Mário Fabrício Fleury Rosa; Yasmin Carneiro Lobo Macedo; Fabiane Hiratsuka Veiga-Souza; Adson Ferreira da Rocha (Journal of Diabetes Research)
The present study aims at evaluating the correlation between the free radical formation and the healing action of lower limbs’ ulcers in a randomized controlled trial with the use of an adhesive derived from natural latex associated with a light-emitting diode (LED) circuit. The sample consists of 15 participants with lower limb lesions divided into three groups: group 1 case (5 participants) received the proposed dressing system adhesive of the natural latex associated with the LED circuit; group 2 control (5 participants) received the dressings at home performed by nurses according to and established by the clinic of wounds (treated with calcium alginate or silver foam); and group 3 (5 participants) also received the dressing in their homes with the use of the dressing adhesive derived from the natural latex associated with the LED circuit. The collected data were analyzed qualitatively and quantitatively by electron paramagnetic resonance for determination of free radical formation. Kruskal-Wallis statistical test was used to evaluate the effect of treatment on the lower limb’s ulcer cicatrization process and its correlation with free radical. The results obtained corroborated the hypothesis about the reduction of the quantity of these molecules in the end of treatment related to the healing wound.